Manajemen Kurikulum Merdeka dalam Meningkatkan Mutu Pendidikan di Smp Negeri 46 Merangin - Robby Hidayat; Yulius Efendi; Riska Meisyi Putri; Anggia Pratiwi (CV. Ulil Albab Corp, 2026)
The implementation of the Independent Curriculum requires effective management to improve the quality of education at the educational unit level. A curriculum that provides flexibility and is student-oriented requires planned, collaborative, and contextual management for optimal implementation. This study aims to understand the implementation of the Independent Curriculum management in improving the quality of education at SMP Negeri 46 Merangin, as well as to identify supporting and inhibiting factors in its implementation. The study used a qualitative descriptive approach with research subjects including the principal, vice principal for curriculum, and teachers. Data were obtained through interviews, observation, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results show that the Independent Curriculum management at SMP Negeri 46 Merangin is implemented through contextual curriculum planning, student-centered learning implementation, and the implementation of the Pancasila Student Profile Strengthening Project. This curriculum management contributes positively to increasing learning activity, learning quality, and strengthening student character. These findings confirm that the targeted and adaptive management of the Independent Curriculum plays a crucial role in achieving quality and sustainable education. Independent Curriculum, Curriculum Management, Education Quality